Evaluating the MBG Monitoring Application in Indonesian Schools Using the DeLone & McLean Model - Maulana, Yono; Rahayu, Agus; Adi Wibowo, Lili; Harisandi, Prasetyo; Advincula, Geraldine B; Prasetyo, Dedi (IJORER : International Journal of Recent Educational Research, 2025)
Objective: The Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) is a strategic initiative by the Indonesian government aimed at enhancing the nutrition of school-age children, with application monitoring playing a key role in its effectiveness. This study assesses the success of the MBG implementation by empirically examining the impact of system quality, human resource (HR) training effectiveness, and strategic leadership support on system adoption and net benefits. Using the DeLone & McLean Information System Success Model (2003) as a theoretical framework. Metode: survey was conducted among MBG application users, including field officers and supervisors. Data were collected through a structured questionnaire measuring system quality, training effectiveness (based on Kirkpatrick’s reaction, learning, and behavior levels), leadership support, system use, user satisfaction, and net benefits. Structural Equation Modeling (SEM) was employed for data analysis. Result: The results indicate that strategic leadership support significantly affects system use, while training effectiveness positively influences net benefits. Novelty: The study’s novelty lies in integrating strategic management and user adoption perspectives within public sector digital initiatives in developing countries.